Nigeria Government’s Expenditure on Economic and Social Service Development: A Canonical Correlation Analysis Approach - , Rafiu Olayinka Akano; , Samuel Olorunfemi Adams (Archives of Current Research International, 2019)
The study examine the effect of Government’s expenditure on economic and social services development in Nigeria over the period of 1961 to 2018. The study used Canonical Correlation Analysis, the test carried out include; Structure Vector for Economic and social Service and Redundancy Index. The result reveals that strong positive relationship exists between national recurrent expenditure and economic service and Social service. The study also discover that Nigeria Government placed more emphasis on other economic services like; Oil and gas, trade, infrastructure and manufacturing, followed by Transport and Communication, Construction, and Agriculture being the least. In the case of the Social service, it was discovered that Nigeria Government placed more emphasis on other social services like; food subsidies, police, fire services, housing, community management, policy research, information and labour, followed by Health, and Education being the least. Based on the findings, the study recommends that, all tiers of government and policy makers should implement policies that will aid improvement in Transportation and Communication, Construction, Agriculture, Health and Education.